The Problem of Supporting the Management of a Growing Multi-Discipline Group of Companies - Mirzayanovna Sadrieva, Liliya; Vladimirovich Tsovma, Denis; Valentinovna Iudina, Svetlana (International Journal of Engineering and Technology, 2018)
The process of growth of corporations and groups of companies has slowed down in Russia since 2008-2009 but has not stopped. Nowadays, a group of companies is usually a poly-industry organization with the presence of none-core companies and companies of the social bloc that is often the result of a trade-off of large business and the government. The task of bringing out the groups of companies of the social bloc into the break-even zone in Russia became acute after 2014 due to a reduction in reserves of profitability growth in the main profitable blocs. It is very difficult for the management of the group of companies to differentiate external risks, some complex system and accidental internal factors of activity of a relatively large number of economic entities and not to lose control of the group as a whole. In the authors' opinion, the development of a methodology for informational support of policy decisions regarding the architecture of a group of companies can be based on well-known concepts (the concept of strategic management) and approaches (systematic and process approaches). Then, the management of the group of companies is presented in the form of a list of competencies with assigned managerial functions of information support of different levels developed by the authors and presented in the paper.Â Â